Perceptions of participants and residents of the impacts of the Braga 2012 European Youth Capital - José Cadima Ribeiro; Paula Remoaldo; Eduardo Duque (European Regional Science Association (ERSA), 2015)
The European Youth Capital is an annual title awarded to a European city by the European Youth Forum, aiming to strength the relationship between the municipalities and the European Union institutions, with a particular focus on youth participation. Until now, little is known about the impacts of hosting a European Youth Capital, being the present investigation the first one dealing with this issue. The relative success of the Braga (Portugal) 2012 European Youth Capital (EYC 2012) is evaluated through the perception of the participants in five events performed. The aim of the questionnaires applied was inquiring the opinion of respondents on the activities of the EYC 2012, as well as the perceived impacts of the mega-event. Additionally, we envisaged to know what had been their participation in it by the time the questionnaire was implemented. A focus group was also implemented. This methodological approach was used to clarify and complement certain dimensions of the data collected through the survey applied to participants. We got a sample of 512 respondents, applying the questionnaires among October and December 2012. From the results obtained, we could conclude that the hosting of the EYC did not attract a large amount of visitors to the city. The younger respondents, who predominate in the sample used (59% between 10 and 29 years old), tended to keep a more positive assessment of the impacts of the EYC 2012, as well as women when compared to men.
Keywords: R11; R58; 330; Mega-events; Perceptions of the participants and residents